Kingdom of Heaven :. - Limerick City Gallery of Art; O'Reilly, Paul M. (Limerick : Limerick City Gallery of Art Limerick, 1999)
Aiken, John ; Armstrong, Arthur ; Barret, George ; Barry, Moyra ; Blodau, Dieter ; Bogan, Vivienne ; Boydell, Cormac ; Brennan, Anne ; Carver, Robert ; Coleman, Simon ; Collie, George ; Collins, Patrick ; Connor, Jerome ; Conor, William ; Cooke, Barrie ; Craig, J. Humbert ; Cross, Dorothy ; Cummings, Cindy ; Davidson, Lilian ; Dixon, Sean ; Doherty, Willie ; Donovan, Jack ; Drummond, Blaise ; Durcan, Sarah ; Farrell, Micheal ; Fitzgerald, Tom ; Fitzpatrick, Mike ; Foley, Marie ; Fox, Kathleen ; Giusti, Karen ; Gorman, Richard ; Guinness, May ; Hamilton, Letitia M. ; Hanlon, Rev Jack P. ; Hare, St. George ; Harper, Charles ; Haverty, Joseph Patrick ; Hayden, Henri ; Hennessy, Patrick ; henry, Grace ; Henry, Paul ; Hogg, Gavin ; Hone, Evie ; Hone, Nathaniel ; Hughes, Ronnie ; Janz, Robert ; Jellett, Mainie ; Jervas, Charles ; Joyce, Mark ; Keating, Sean ; Kelly, Sir Gerard ; Kernoff, Harry ; King, Cecil ; de Kooning, Willem ; Lamb, Charles ; Lambert, Gene ; Lavery, Sir John ; Leech, William J. ; MacGonigal, Maurice ; Maclise, Daniel ; Martin, Fergus ; Martyn, Ferenc ; McHugh, John ; McKelvey, Frank ; Mulcahy, Jeremiah Hodges ; Mullarney, Janet ; Mulready, William ; Nash, David ; O'Brien, Cecily Maud ; O'Brien, Dermod ; O'Carroll, Anthony ; O'Casey, Breon ; O'Connor, Arthur James ; O'Mahony, Deirdre ; O'Sullivan, Sean ; Orpen, Sir William ; Osborne, Walter ; Purser, Sarah ; Pye, Patrick ; Reid, Nano ; Rolfe, Nigel ; Rosenquist, James ; Ryan, Sarah ; Ryan, Thomas ; Sheehy, Jim ; Sheppard, Oliver ; Shinnors, John ; Shore, Robert A. ; Slade, Richard ; Sleator, James S. ; Souter, Camille ; Stein, Amelia ; Stephenson, Desmond ; Swanzy, Mary ; Tutty, Benedict ; Verling, Walter ; Walsh, Samuel ; Warren, Michael ; West, Katharine ; Wilks, Maurice C. ; Yeats, Jack B. ; etc.
biog. p. 170-183
Kingdom of Heaven : Selected juxtapositions, old and new, drawn from the permanent collection of Limerick City Gallery of Art, 1999
Engels
boek